Correlation among Sodium Intake, Fat Intake and Physical Activity with Prevalence of Hypertension in Young Adults at Arifin Achmad Regional Public Hospital, Riau - Annisa Amalia Huzaipah; Evawany Yunita Aritonang; Rahayu Lubis (Journal of Epidemiology and Public Health, 2020)
Background: Hypertension is called the silent killer for it has high prevalence rate and is asymptomatic; thus, it needs to be early prevented. When blood pressure is high and uncontrollable, it may lead to complications. Today, hypertension is not only found in elderly, it is also found among young adults at age > 18 and it tends to increase annually as they frequently consume high sodium and high fat and lack of physical activities along with the development of technology. Developed technology has made everything easy to do without burning excessive energy. More researches on hypertension are conducted on elderly and only a few are conducted on young adults. The objective of this study is to discover the correlation among sodium intake, fat intake, and physical activity with prevalence of hypertension in young adults at Arifin Achmad Regional Public Hospital, Riau Province.Subjects and Method: This is an analytical observational study with case-control design that was carried out at Arifin Achmad Regional Public Hospital, Riau Province, Indonesia. A sample of 80 respondents divided into a case group with 40 respondents and control group with 40 respondents was selected by purposive sampling. The depen